MOVEMENT OF STOCK MARKETS IN INDIA: INFLUENCE OF MACROECONOMIC FACTORS - Dr. Hari Leela Vemula (Galaxy International Interdisciplinary Research Journal, 2021)
In modern times, stock markets are considered to be important part of financial markets and it reveals the health of the economy. In fact, they are also referred to as barometer of an economy. Share prices do not move in vacuum rather their movement is affected by a large number of heterogeneous factors. The main objective of the study is to identify important factors that affect the movement of Indian stock markets and the degree of impact of these factors on the same. For conducting this study, BSE Sensex has been used to represent the movement of stock market in India. The study deals with time series data and consist of ten variables i.e. Crude Oil Prices, FII Investment, Foreign Exchange(USD/INR)Rate, Foreign Exchange Reserve, Inflation (Wholesale Price Index as a proxy for inflation), S&P 500, NASDAQ Composite, FTSE 100, Nikkei 225, and BSE Sensex. Principal Component Analysis and Regression Analysis are used in the study to draw the conclusions. All these variables have been clubbed into two broad factors labeled as Factor1 (F1) and Factor2 (F2). The study reveals that both these factors have significant impact on movement of BSE Sensex.